Acute pancreatitis complicated by encephalopathy - Jhamb, Rajat; Parasher, Anant; Baweja, Ashish (International Journal of Research in Medical Sciences, 2020)
Pancreatic encephalopathy is a frequently under-diagnosed and rare complication of acute pancreatitis. It denotes the occurrence of neuropsychiatric abnormalities in the setting of acute pancreatic inflammation, and presents with neurological symptoms that may persist even after the resolution of all metabolic parameters. Here we present the case of a 42 year old male patient presenting with altered sensorium and focal neurological deficit during the course of acute pancreatitis. The patient was treated conservatively, and later improved with supportive care.